Die Boek van die Twaalf: ’n Kort oorsig - O’Kennedy, DF (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The Book of the Twelve: A Short Survey For the past two decades scholars have shown renewed interest in the last twelve prophetic books of the Old Testament. Several research articles and books were published, especially from the SBL seminars on the Formation of the Book of the Twelve. Many scholars agree that the Book of the Twelve must be read as an unified whole. A few questions may be posed: Do the research articles in South Africa reflect this renewed interest? Do we experience the effect of this research in the church and popular biblical publications? The author concludes that the Book of the Twelve is still neglected in South Africa, in the academic field as well as in churches. A short survey of the Twelve is presented in Afrikaans to highlight the value of recent research. The Twelve is discussed in the following sections: Early witnesses and the name “Book of the Twelve”; Socio-historical background to the Twelve; Recent research on the Twelve; Order of the books and placing in different canons; and theological message.